Bidirectional Targeted Killing approach of Genetically Engineered Escherichia coli surface antigen (fimbriae) BNT (Bionanotube) to tumor cell : A Molecular and Engineering Design Concept of Cancer Therapy. Issue 3 (2017) - Brahma, Nitosh Kumar
No abstract available